2018
DOI: 10.1002/cm.21488
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microtubule plus end dynamics by septin 9

Abstract: Septins are GTP-binding proteins that associate with the microtubule (MT) and actin cytoskeleton. Septins affect MT organization and posttranslational modifications, but their role in MT dynamics is less understood. Here, we reconstituted MT dynamics in the presence of the MT-binding septin (SEPT9) using an in vitro cell-free assay, which images the polymerization of tubulin from guanosine-5'-[(α,β)-methyleno]triphosphate (GMPCPP)-stabilized MT seeds. We found that submicromolar concentrations of SEPT9 suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 38 publications
2
39
0
1
Order By: Relevance
“…This is therefore likely to be a 'promiscuous' interaction as seen in many other septin crystal structures. Nevertheless, recent evidence suggests that a homotypic G interface formed by SEPT9 may be physiologically important in the control of microtubule dynamics (Nakos et al, 2019).…”
Section: The G and Nc Interfaces Of The Sept3 Subgroupmentioning
confidence: 99%
“…This is therefore likely to be a 'promiscuous' interaction as seen in many other septin crystal structures. Nevertheless, recent evidence suggests that a homotypic G interface formed by SEPT9 may be physiologically important in the control of microtubule dynamics (Nakos et al, 2019).…”
Section: The G and Nc Interfaces Of The Sept3 Subgroupmentioning
confidence: 99%
“…Given that MT growth and dynamics are inhibited by higher concentrations of SEPT2/6/7 (>800 nM), we asked whether higher-order SEPT2/6/7 complexes associate with free unpolymerized tubulin, lowering the effective concentration of tubulin that is available to polymerize. This is plausible as we recently found that SEPT9 binds and recruits free tubulin to the MT lattice (Nakos et al, 2019). To test this possibility, SEPT2/6/7 and SEPT9 complexes were immobilized on functionalized glass chambers and fluorescent tubulin was added in the buffer conditions of the MT dynamics assay ( Figure S2a).…”
mentioning
confidence: 86%
“…(Nakos et al, 2019; Reid et al, 2016;Tanenbaum et al, 2013). TIRF imaging was performed as described before(Nakos et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding of these mechanistic differences is important as the assembly and association of these higher order components with cell membranes, actin filaments, and microtubules are fundamentally tied to septin cellular function. 24,[49][50][51][52][53][54][55] Septin hetero-hexamers and hetero-octamers both form in mammalian cells with the heterooctamers typically being the dominant species. 41,42 While the cell biology of mammalian septins is advancing rapidly (see above) and the biophysical basis of yeast septin assembly is progressing, [56][57][58][59][60][61] biochemical and biophysical studies of mammalian septins have lagged due to the lack of a mammalian hetero-octamer purification.…”
Section: Introductionmentioning
confidence: 99%